Continuous wet-spinning of flexible and water-stable conductive PEDOT: PSS/PVA composite fibers for wearable sensors. (February 2020) - Gao, Qiang; Wang, Mingxu; Kang, Xinyuan; Zhu, Chunhong; Ge, Mingqiao
Abstract: A conductive composite fiber of poly(3, 4-ethylenedioxythiophene): poly (styrene sulfonate) (PEDOT: PSS) and polyvinyl alcohol (PVA) was synthesized via a wet-spinning method. Especially, conductivity loss owing to the addition of PVA was compensated by using a solvent treatment method with ethylene glycol (EG). Compared with pristine PEDOT: PSS fibers, PEDOT: PSS/PVA/EG conductive composite fibers exhibited enhanced flexibility. The optimal tensile strength and elongation at break, 210 ± 5 MPa and 26 ± 1.5% respectively, were obtained for the conductive fibers with the addition of 20 wt% PVA and 10 wt% EG. Meanwhile, the resultant composite fiber revealed a good recovery behavior of the strain and electroconductivity within the strain of 20%. PEDOT: PSS composite fibers reveal a good durability of electroconductivity in water even under a strain. A series of strain sensing fabrics were designed based on the composite fibers. Results of various proof-of-concept experiments indicated that this PEDOT: PSS/PVA/EG composite conductive fiber is a promising candidate for flexible intelligent textiles, which can be used for fast response and sensitive wearable sensors for monitoring body motions and real-time health. Highlights: Continuous PEDOT: PSS/PVA composite fibers without cracks were prepared. Resultant fibers reveal a good durability of electroconductivity in water even under a strain. Composite fibers presented better tensile mechanical properties and processability. Knitted fabrics of composite conductive fibers were used to monitor the motion of human body.